Are perceived containment and coping styles differentially associated with reactive and proactive aggression?. Issue 3 (10th December 2022) - Baca, Selena A.; Fite, Paula J.; Chang, Chi‐Ning
Abstract: Studies informing ways to target aggression in youth, particularly through the identification of internal patterns predictive of concurrent and future levels of aggression, could be particularly beneficial. To this end, the current study surveyed 216 elementary‐aged children on topics of perceived containment (i.e., perceived ability of authority figures to control, limit, and set consequences for one's behaviors), coping responses, and reactive (RA) and proactive aggression (PA). Using multilevel modeling, the individual and interactive effects of coping responses and perceived containment on aggression within time and across two school years were examined. Within time, lower levels of perceived containment were associated with greater RA and PA. Passive coping was also positively associated with RA. The relation between perceived containment and RA within time was dependent on humor, whereas the relation between perceived containment and PA depended on problem‐solving. Across time, while T1 passive coping predicted the trajectory of both functions of aggression, a greater number of T1 coping responses predicted the slope of RA with problem‐solving and friend support‐seeking as well as T1 perceived containment also predicting the trajectory of RA. No coping responses moderated the relation between T1 perceived containment and the trajectory of RA. In contrast, humor moderated the influence of T1 perceived containment and the trajectory of PA. Findings give insight into the ways internal processes of perceived containment and coping are associated with patterns of aggression in elementary‐aged youth. This work is valuable in identifying several potential areas for prevention and intervention research.